Karir atau Hubungan, Manakah Pilihanku? Pengambilan Keputusan Menikah Pada Wanita Karir - Repi, Andhika Alexander; Maliombo, Nadia Evangelista (Psychopreneur Journal, 2022)
For women, marriage is a form of fulfilment of ’traditional demands’ in entering into their roles as wives and mothers. The rapid changes of the times has created another phenomenon that not infrequently women aged above early adulthood make decisions to put marriage aside, especially for career women. This study aims to dive deeper into the picture of decision making regarding marriage in career women. Phenomenology and Inductive Thematic Analysis are used as methods and data analysis techniques so that phenomena can be captured deeply to identify decision making related to marriage that is experienced and felt from the point of view of the informant. RI (28 years old) and SDR (40 years old) who are informants of this study have different family and work backgrounds. The results showed, both informants had hopes of staying married. However, there are a number of personal reasons for the two to finally decide not to get married yet. Decisions taken by informants go through level of stages, starting from observation and evaluation of experience, determining alternatives, and finally determining decisions. There are various factors that play a role in the decision-making process and results of the informants, which is internal and external factors.